Structure-to-function relationships of bacterial translocator protein (TSPO): a focus on Pseudomonas - Leneveu-Jenvrin, Charlène; Connil, Nathalie; Bouffartigues, Emeline; Papadopoulos, Vassilios; Feuilloley, Marc G. J.; Chevalier, Sylvie (Frontiers in Microbiology, 2014)
The translocator protein (TSPO), which was previously designated as the peripheral-type benzodiazepine receptor, is a 3.5 billion year-old evolutionarily conserved protein expressed by most Eukarya, Archae and Bacteria, but its organization and functions differ remarkably. By taking advantage of the genomic data available on TSPO, we focused on bacterial TSPO and attempted to define functions of TSPO in Pseudomonas via in silico approaches. A tspo ortholog has been identified in several fluorescent Pseudomonas. This protein presents putative binding motifs for cholesterol and PK 11195, which is a specific drug ligand of mitochondrial TSPO. While it is a common surface distribution, the sense of insertion and membrane localization differ between α- and γ-proteobacteria. Experimental published data and STRING analysis of common TSPO partners in fluorescent Pseudomonas indicate a potential role of TSPO in the oxidative stress response, iron homeostasis and virulence expression. In these bacteria, TSPO could also take part in signal transduction and in the preservation of membrane integrity.